Dilution Effect on the Investigation of Soil Organic Matter Quality in UV-VIS Spectra - Sebők, András; Czikota, Imre; Dálnoki, Anna Boglárka; Gulyás, Miklós; Lehoczky, Éva; Tury, Rita; Takács, Anita (Journal of Central European Green Innovation, 2023)
Soil organic matter is a factor in many areas. Its knowledge helps to develop more accurate models and to use more effective predictions and estimates. While the quantity of organic matter can be well characterised, determining soil organic matter quality is a major challenge. Several methods (mainly based on spectral analysis of organic matter extracts) have been developed, such as the E4/6 [465/665 nm] or E2/3 [250/365 nm] ratios. The ultraviolet and visible light (UV-VIS) spectra of the extracts (200-900 nm) form exponential curves, from which the ratio derived from the data measured at selected points provides information on the molecular size distribution of the organic matter (ratio of humic acids to fulvic acids). The conventional E4/6 values generally give good results for the qualitative distribution of organic matter. If the samples contain some interfering factor, conventional calculations based on the ratio of the two points can be problematic. However, our EFA (Exponential Fitting Approach) method gives much more reliable and repeatable results by fitting hundreds of points. EFA is less sensitive to dilution differences in samples, which has proven to be more reliable (or at least as good) than the conventional method. Therefore, its use can improve the accuracy and repeatability of organic matter quality determination.